AFM assessing of nanomechanical fingerprints for cancer early diagnosis and classification: from single cell to tissue level. Issue 45 (8th November 2018) - Stylianou, Andreas; Lekka, Malgorzata; Stylianopoulos, Triantafyllos
Abstract : AFM measurements could be employed to complement standard biopsy procedures, offering an objective, novel and quantitative diagnostic approach with the properties of a blind assay, allowing unbiased evaluation of the sample. Abstract : Cancer development and progression are closely associated with changes both in the mechano-cellular phenotype of cancer and stromal cells and in the extracellular matrix (ECM) structure, composition, and mechanics. In this paper, we review the use of atomic force microscopy (AFM) as a tool for assessing the nanomechanical fingerprints of solid tumors, so as to be potentially used as a diagnostic biomarker for more accurate identification and early cancer grading/classification. The development of such a methodology is expected to provide new insights and a novel approach for cancer diagnosis. We propose that AFM measurements could be employed to complement standard biopsy procedures, offering an objective, novel and quantitative diagnostic approach with the properties of a blind assay, allowing unbiased evaluation of the sample.